KOMITMEN PERUSAHAAN BUS AKAP DAN PARIWISATA TERHADAP PENERAPAN STANDAR KESELAMATAN LALU LINTAS DAN ANGKUTAN JALAN - Rehani Fitria (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2017)
This study aims to analyze the commitment of intercity bus operator PT. Rosalia Indah Transport and tourist bus at PT. Duta Bangsa Transport on the application of Traffic Safety Standards and Road Transportation based on Ministerial Regulation No. 26 of 2015 and No. 29 of 2015 and the implementation of Safety Management System (SMK) based on Law no. 22 Year 2009 article 204 paragraph 1. This research uses descriptive-qualitative method. The results show PT. Rosalia Indah Transport has a high commitment to safety by complying with the safety standard rules contained in Ministerial Regulation No. 26 of 2015 and No. 29 of 2015, and PT. Duta Bangsa Transport shows its commitment to safety by complying with the standard safety rules contained in PM 26 of 2015 and PM 29 of 2015. PT. Rosalia Indah Transport has shown its commitment to the implementation of Law No. 22 of 2009 article 204 paragraph 1 by establishing, implementing and improving the safety management system.